On commodities, networks and imaginaries. Reflections based on a interdisciplinary dialogue surrounding the local scientific practice - Córdoba, María Soledad; Buccellato, Marcos; Bilañski, Gisele; Smal, Clara; Guzzo, Daniel; Azcurra, Karen (Instituto de Altos Estudios Sociales, 2018)
This article is the result of meetings between those who carry out scientific research or technological development and those who study the work of science and of scientists. The effort to understand ourselves from the different perspectives we adhere to, resulted in a critical and interdisciplinary dialogue on the social, political and economic conditions of the production of scientific and technological knowledge. In particular, this exercise allowed us to reflect analytically on the conditions under which science is currently made: the powerful relationship with the market and capital within the framework of a network of institutions and under the necessary construction of socio-cultural imaginaries to the permanent development of innovations. These three aspects are developed in this article and will be analyzed by intersecting the notion of General Intellect developed in the Grundisse and its appropriation by the theoretical perspective of "cognitive capitalism", with the Habermasian reformulation of the Lebenswelt (world of lifetime).